2014
DOI: 10.1016/j.gie.2014.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance and suboptimal bowel preparation with split-dose bowel regimen in average-risk screening colonoscopy

Abstract: Background Although split-dose bowel regimen is recommended in colon cancer screening and surveillance guidelines, implementation in clinical practice has seemingly lagged because of concerns of patient compliance. Objectives To assess patient compliance with the split-dose bowel regimen and assess patient- and preparation process–related factors associated with compliance and bowel preparation adequacy. Design Prospective survey cohort. Setting Tertiary care setting. Patients Average-risk patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 26 publications
(27 reference statements)
0
47
0
Order By: Relevance
“…However, a split-dose regimen can result in sleep disturbance and fecal incontinence during transit to the endoscopy center [3,6] . A recent study reported that 1 in 7 patients does not comply with a split-dose bowel regimen [7] . Although the use of split-dosage preparations is suggested for elderly patients [8] , supporting evidence is lacking for this population.…”
Section: Introductionmentioning
confidence: 99%
“…However, a split-dose regimen can result in sleep disturbance and fecal incontinence during transit to the endoscopy center [3,6] . A recent study reported that 1 in 7 patients does not comply with a split-dose bowel regimen [7] . Although the use of split-dosage preparations is suggested for elderly patients [8] , supporting evidence is lacking for this population.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was found that 1 in 7 individuals did not comply with a split dose bowel preparation. A compliance with the splitdose bowel regimen will reduce the risk of a suboptimal bowel preparation [43]. The results of another study, also, revealed that split-dose bowel preparation resulted in better bowel cleansing, and improved patient tolerance [44].…”
Section: Bowel Preparationmentioning
confidence: 98%
“…The literature suggests that split dose preparations are more effective and better tolerated by patients in general [13,14]. On the other hand patient compliance with split dose prep can be an issue [15]. Keeping these factors in mind and especially noting that many our patients travel up to 3 hours for their procedures we chose to start spit dose preparations for colonoscopies starting after noon (12 PM).…”
Section: Colonoscopy Preparationmentioning
confidence: 99%